1989
DOI: 10.1152/jappl.1989.67.1.264
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory response to rowing and cycling in elite oarswomen

Abstract: Rowing is a unique exercise for humans, and the imposed biomechanical motion may alter both respiratory mechanics and timing. To investigate the ventilatory patterns of competitive rowers while rowing, we studied the pulmonary function of eight members of the University of Washington Women's Crew and one former member of the 1984 Women's Olympic Rowing Team on a rowing ergometer. Ventilatory performance of the oarswomen was compared both with their performance to exhaustion on a cycle ergometer and with the ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…The hypothesis that entrainment of breathing improves the effectiveness of rowing has even been examined (Maclennan et al 1991;Steinacker et al 1993). Szal and Schoene (1989) found that rowing causes hyperventilation with higher breathing rate and lower tidal volume than cycling. These results were observed in both oarswomen and agematched untrained non-rower women.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis that entrainment of breathing improves the effectiveness of rowing has even been examined (Maclennan et al 1991;Steinacker et al 1993). Szal and Schoene (1989) found that rowing causes hyperventilation with higher breathing rate and lower tidal volume than cycling. These results were observed in both oarswomen and agematched untrained non-rower women.…”
Section: Discussionmentioning
confidence: 99%
“…For example, rowing elicits strokeby-stroke fluctuations in blood pressure and CBF, 125 and the biomechanical motion of rowing provokes changes in respiratory mechanics including timing of breaths during the stroke, 126 which has been shown to uncouple the CBF response from the normal hyperventilation-induced hypocapnic lowering of CBF above 70% _ VO 2 max; CBF velocity in the MCA increased further during a 30-second sprint performance despite the lowering of the end-tidal PCO 2 .…”
Section: Optimizing Cerebrovascular Adaptation and Safety For High-inmentioning
confidence: 99%
“…For heavy exercise leading to production of lactic acid,V E increases proportionately more thanV O 2 andV CO 2 . The slope of theV E -V O 2 orV CO 2 relationships are influenced by such conditions as exercise type (88,193,232,319), posture (88), muscle mass (16), acid-base status (121,259), levels of oxygenation (84,89,125), and levels of certain hormones or neurotransmitters (197,242,272,293). These relationships are less well established for non-human mammals, but based on changes in PaCO 2 (presented below), it appears that in most non-human species,V E increases during exercise proportionately more thanV O 2 andV CO 2 .…”
Section: Characteristics Of the Exercise Hyperpneamentioning
confidence: 99%
“…In non-human species, PaCO 2 homeostasis is not maintained during submaximal exercise ( Fig. 2) (47,70,116,124,130,195,203,241,263,264,281,302,319). Ponies ( Fig.…”
Section: Arterial Blood Gases During Constant Load Exercisementioning
confidence: 99%